2015
DOI: 10.1111/pbi.12418
|View full text |Cite
|
Sign up to set email alerts
|

Interspecies gene transfer provides soybean resistance to a fungal pathogen

Abstract: SummaryFungal pathogens pose a major challenge to global crop production. Crop varieties that resist disease present the best defence and offer an alternative to chemical fungicides. Exploiting durable nonhost resistance (NHR) for crop protection often requires identification and transfer of NHR‐linked genes to the target crop. Here, we identify genes associated with NHR of Arabidopsis thaliana to Phakopsora pachyrhizi, the causative agent of the devastating fungal disease called Asian soybean rust. We transfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 46 publications
0
37
0
Order By: Relevance
“…Similarly, the rice receptor-like kinase (RLK) gene Xa21 has been shown to provide Banana Xanthomonas wilt resistance in banana (Tripathi et al 2014). The nonhost resistance NHR-linked Arabidopsis genes PING 4 (coding for a phospholipase-like protein (EARLI4-like)), PING 5 (coding for a leucine-rich repeat protein kinase) and PING 6 (coding for an ankyrin repeat family protein), known to provide pre-invasion resistance to nonadapted fungal pathogens, have been transferred into soya bean where they confer Asian soya bean rust resistance (Langenbach et al, 2016). Lr34res also has been successfully transferred in other crop species such as barley and rice Risk et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the rice receptor-like kinase (RLK) gene Xa21 has been shown to provide Banana Xanthomonas wilt resistance in banana (Tripathi et al 2014). The nonhost resistance NHR-linked Arabidopsis genes PING 4 (coding for a phospholipase-like protein (EARLI4-like)), PING 5 (coding for a leucine-rich repeat protein kinase) and PING 6 (coding for an ankyrin repeat family protein), known to provide pre-invasion resistance to nonadapted fungal pathogens, have been transferred into soya bean where they confer Asian soya bean rust resistance (Langenbach et al, 2016). Lr34res also has been successfully transferred in other crop species such as barley and rice Risk et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the feasibility of transferring single NHR-related genes across plant species to create durable, broad-spectrum resistance (Brutus and He, 2010; Wen et al, 2011; Schoonbeek et al, 2015; Langenbach et al, 2016). The mechanisms of rice resistance to Pst can be used to improve wheat resistance.…”
Section: Discussionmentioning
confidence: 99%
“…For example, NHR of Arabidopsis and Medicago to bean rust (Patto and Rubiales, 2014; Ishiga et al, 2015; Langenbach et al, 2016), barley and Brachypodium distachyon NHR to cereal rust pathogens (Zellerhoff et al, 2010; Dawson et al, 2015; Figueroa et al, 2015; Niks et al, 2015a). As the model of monocotyledonous plant, rice is unusual in not being affected by a rust pathogen (Ayliffe et al, 2011b).…”
Section: Introductionmentioning
confidence: 99%
“…To compare the activation pattern of PPP routes in the Arabidopsis non-host and soybean host we first monitored the expression of genes potentially involved in scopoletin and flavonoid biosynthesis in the SBR-susceptible soybean cultivar Williams 82 (W82) after inoculation with the highly virulent Pp isolate BR05 (Langenbach et al, 2016b). Consistent with an earlier report (Schneider et al, 2011) we detected biphasic induction of PPP genes in the soybean PAL, C4H and CHS families with an early expression peak at 12-24 h post inoculation (hpi) and a late expression maximum at 144-216 hpi ( Figure 2).…”
Section: Scopoletin Is Absent From Leaves Of Both Sbr-susceptible Andmentioning
confidence: 99%